A Forensic Aspect of Fetal Shoulder Dystocia - Habek, Dubravko; Cerovac, Anis (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Fetal shoulder dystocia (FSD) is an unpredictable and critical obstetric intrapartum emergency, where an objective problem is the relationship between the mother's pelvis and the child, i. e., an anthropometric disorder of delivery mechanics and dynamics. It is evident that the need to perform other maneuvers indicates the severity of FSD, which in turn correlates with the consequent iatrogenic injury of the fetus and/or mother. FSD is certainly the most controversial forensic obstetric problem, with the most disputes, compensation for damages due to peripartum injury to the child and/or mother, pain suffered, the need for someone else's care, and permanent disability. Suboptimal procedures and inadequate documentation are factors of forensic risk and subsequent litigations. Prevention of FSD is generally not possible, although good antenatal care can sometimes exclude risky cases of FSD, and some rare, chronic intrauterine disorders can result in orthopedic and neurological sequelae, which is especially important in forensic analysis. Because FSD is largely impossible to predict, it must be viewed as an intrapartum acceptable risk. During childbirth, FSD may compromise the safety of the mother and unborn child, therefore education and skills acquisition are necessary for obstetric work. Risk control, proper procedures, and proper documentation, along with good communication with the pregnant women and their families, significantly reduce litigation procedures.
Keywords: shoulder dystocia; forensic; clinical risk